DNAClinSUS v1: A Decision Support System to Identify Clinically Relevant Variants in Microarray Genotypes Using Panel-Based Reporting - Ferreira Júnior, Paulo Roberto; Brisolara, Lisane Brisolara de; Gonzalez, HugoCarlos Bolzon; Morales-Pison, Sebastián; Fernández-Ramires, Ricardo; Campos, Vinicius Farias; Demarco, Flavio Fernando (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2026: Anais do XXVI Simpósio Brasileiro de Computação Aplicada à SaúdeDO - 10.5753/sbcas.2026.21042, 2026)
Translational genomics workflows still face a persistent operational gap between genotyping outputs and clinically usable, auditable interpretations: in many settings, results remain scattered across spreadsheets, ad hoc queries, and external websites, making reporting difficult to reproduce and to trace back to supporting evidence. DNAClinSUS v1 is a web-based clinical decision support system developed in the context of a SUS-oriented precision public health initiative in Brazil to address this gap by operationalizing a pragmatic genotype-to-report workflow in environments where patient genotypes are already available from microarray platforms. In its current version, DNAClinSUS v1 ingests single-individual CSV genotype files from microarrays, deterministically aligns SNP calls using array-manifest references, and supports panel-oriented interpretation through a locally managed knowledge base of genes and ClinVar-linked variants. The platform enables first-class curation and reuse of gene-based panels, supports SNP and polygenic panels via direct import of scoring files, and generates patient reports, as well as variant-level drill-down with links to external evidence resources. This paper presents DNAClinSUS v1 and discusses its constraints and requirements, data model, and the implemented workflow, emphasizing software engineering design choices and outlining its role as a concrete baseline that can be extended in future versions.